Pengaruh Likiuditas, Profitabilitas, Kecukupan Modal dan Resiko Kredit terhadap Nilai Perusahaan - Akris Diantoro, Femba (INAIFAS Press, 2024)
This research aims to determine the influence of liquidity, profitability, capital adequacy and credit risk on company value in the conventional banking sector listed on the Indonesia Stock Exchange. The analytical method used in the research is multiple regression with the help of SPSS (Statistical Program for Social Science). The population in the research is the conventional banking sector listed on the Indonesia Stock Exchange in the 2018 - 2022 period with a total of 43 companies. The method used for the sample used purposive sampling. The results of the research show that liquidity has a negative effect on company value, profitability has no effect on company value, capital adequacy is proxied by the Capital Adequacy Ratio having a positive relationship and has no significant effect on company value, and where Non-Performing loans have an effect on company value. The implications of banking companies for issuers in Indonesia are the importance of awareness in growing company value by considering all aspects of liabilities because it will refer to the direction of financial position, as well as taking into account the adequacy of credit reserves as an indicator of the health of banking asset quality